Application of hybrid real-time simulation concept for modeling of HVDC back-to-back link; AIP Conference Proceedings; Vol. 2135 : Heat and mass transfer in the thermal control system of technical and technological energy equipment (HMTTSC 2019) - Rudnik V. E. Vladimir Evgenevich (2019, 2019)
Title screen